HUBUNGAN POWER OTOT TUNGKAI TERHADAP KECEPATAN TENDANGAN T PADA ATLIT PENCAK SILAT DIKLAT BINAAN DISPORA ACEH TAHUN 2018 - Munzir Mun Munzir (Universitas Syiah Kuala, 2022)
The purpose of this study was to find out how much influence the leg muscle power had on the speed of the T kick on the pencak silat athletes trained by the Aceh Dispora in 2018. This type of research is quantitative research, namely systematic scientific research on the parts and phenomena and their relationships. The method used in this research is correlational research. In this study, the population used was the Pencak Silat Athletes fostered by the Aceh Dispora which amounted to 11 people. The sampling technique is total sampling. Based on the results of research and data processing of leg muscle power test with kick speed T, it can be produced as follows; The correlation between leg muscle power and T kick speed in pencak silat athletes trained by the Aceh Dispora in 2018 was 0.44. and from the interpretation table it can be stated that leg muscle power (leg dynamometer) has no relationship with kick speed T of 1.47. As well as testing the r-table and r-count obtained 1.47 0.60, namely the r-count is greater than the r-table, thus there is a relationship between limb muscle power and T kick speed in pencak silat athletes trained by the Aceh Dispora in 2018. In this case, the results of the study show a significant relationship between leg muscle power and T kick speed.